THE IMPROVEMENT OF PREDICT AND CLASSIFYING SKILL IN OXIDATION-REDUCTION REACTION MATERIAL THROUGH PREDICT-OBSERVE-EXPLAIN (POE) LEARNING MODEL - reniwati reniwati; chansyanah diawati; ila rosilawati (Universitas Lampung, 2012)
The objective of this research is to describe effectiveness of effectiveness predict-observe-explain(POE) learning model in oxidation-reduction reaction material in improving skill in predict and classifying. The effectiveness of the POE learning model in this research is indicated by the significant difference between experiment classroom and control classroom.Population in this research was all 105 grade X students in Paramarta 1 Seputih Senior High School in academic year 2011-2012 which were distributed in classroom X1, X2, and X3. Samples in this research were classroom X1 as the experiment classroom using POE learning model and classroom X2 as control using conventional learning. Samples were taken using purposive sampling. The research results showed that the n-gain average value of skill in predict in control and experiment classrooms were 0.30 and 0.46 respectively, and the n-gain average value for skill in classifying for control and experiment classrooms were 0.37 and 0.64 respectively.Results of hypothesis test showed that classroom with POE learning model had higher skills in predict and classifying compared with control classroom. This indicated that POE learning model was more effective to improve skills in predict and classifying. Keywords: predict-observe-explain (POE), skills in predict and classifying